2015
DOI: 10.4141/cjps-2014-329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term manure application on mineral composition of irrigated barley silage

Abstract: X. 2015. Influence of long-term manure application on mineral composition of irrigated barley silage. Can. J. Plant Sci. 95: 759Á770. The long-term effect of land application of manure type (composted vs. stockpiled manure), bedding type (wood-chips vs. straw), and application rate on feed quality of barley silage as feed for beef cattle is unknown. We measured selected minerals [P, Ca, Ca:P ratio, Mg, K, K:(Ca'Mg) ratio, Na, Fe, Mn, Zn (1 dry wt.). The treatments also included an unamended control and inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Differences in mineral content across forages depend on many factors such as plant species, growth environment, and fertilizer application [2]. In addition, Miller et al (2015) investigated the impact of longterm manure application on the mineral composition of irrigated barley silage and found that with a greater application rate, concentrations of P, K, Na, and K to Ca + Mg ratio increased, but Ca and Mg concentrations decreased at higher rates compared to a low rate [39]. More studies on minerals are needed to increase our understanding of their changes during ensiling.…”
Section: Tablementioning
confidence: 99%
“…Differences in mineral content across forages depend on many factors such as plant species, growth environment, and fertilizer application [2]. In addition, Miller et al (2015) investigated the impact of longterm manure application on the mineral composition of irrigated barley silage and found that with a greater application rate, concentrations of P, K, Na, and K to Ca + Mg ratio increased, but Ca and Mg concentrations decreased at higher rates compared to a low rate [39]. More studies on minerals are needed to increase our understanding of their changes during ensiling.…”
Section: Tablementioning
confidence: 99%